Geocronologia U-Pb e geoquímica isotópica Hf-Nd do Granito Porto Grande, centro-leste do Amapá - BATISTA, Pedro Henrique Magalhães (2022)
In the southeastern Guiana Shield occurs an Archean continental block so called Amapá Block, which was reworked during the Transamazonian orogenic cycle (2,26 - 1.95 Ga). This tectonic segment consists of Archean granulitic-migmatitic-gneiss complex and granitoids, and Paleoproterozoic greenstone belts and granitoids Among these latter, there is Granite Porto Grande (GPG), recently mapped by CPRM-SUREG-BE on Macapá sheet (1: 250,000). GPG consists of deformed syenogranites and monzogranites, with a prominent mylonitic foliation superimposed on features of magmatic flow and dated at 1842 ± 23 Ma by evaporation of Pb in zircon. Dispersion problems and elevated analytics uncertainties denote caution in the use of this age. In addition, the occurrence of deformed granites with post-transamazonian age is unusual in this region. This work aims to determine the tectonic meaning of the GPG in relation to Transamazonian orogeny through tectonic characterization by petrographic, geochemical and isotopic data (zircon U-Pb and Lu-Hf by LA-ICP-MS and whole-rock Sm-Nd by TIMS). Petrographically, four biotite syenogranites were studied, which presented features of ductile deformation by mylonitic foliation. The geochemical data provided a high-K calcium-alkaline, peraluminous, partially ferrous signature in a typical series of peraluminous leucogranites, with HFSE enrichment, LREE fractionation and negative Eu anomaly. Geotectonic diagrams denote a post-to sin-collisional environment for these granites. The geochronological results for two samples of the GPG provided 207Pb/206Pb weighted average ages in 2078 ± 17 Ma and 2076 ± 20 Ma, who repositioned it in the Rhyacian of Amapá Block and allow a temporal correlation with the granites of the Vila Bom Jesus suite (2.08-2.09 Ga). Mesorhyacian (~ 2.20 Ga) and Neoarchean inheritances (~ 2.57 Ga) were also recorded in zircon U-Pb analyzes. Hf-Nd isotopic signature indicates Mesoarchean model ages (Nd-TDM: 2.8 -2.9 Ga and Hf-TDMC: 3.1 - 3.6 Ga) and subcondritic petrogenetic parameters (ƐNd-Hf(t) < 0), which indicate dominance of crustal rework. In addition, this data indicates to mixture of magmatic sources with a strong contribution of Archaean crustal components into the GPG genesis. Finally, the set of data obtained points to a syn-to late-tectonic magmatism, in relation to Transamazonian orogeny.